2010
DOI: 10.1007/bf03379562
|View full text |Cite
|
Sign up to set email alerts
|

Somatoform Dissociation and Symptoms of Traumatic Stress in Adolescents

Abstract: Dissociation is traditionally attributed to trauma and other psychological stressors although there is evidence that in many cases dissociative symptoms could be attributable to initial brain insult, injury or other organic brain disease. With respect to these findings there is a question to which extent symptoms of somatoform dissociation are related to symptoms of traumatic stress or whether these symptoms may be predominantly attributed to various somatic factors. With this aim we have assessed the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Somatoform dissociative symptoms were measured using 20-items self-reported Somatoform Dissociation Questionnaire (SDQ-20). 11 , 12 Normative score of the scale defines significant occurrence of somatoform dissociative symptoms for scores >30. Somatoform dissociative symptoms represent alterations in sensations of pain (analgesia, kinesthetic anesthesia), alterations of perception, loss of motor control, gastrointestinal symptoms, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Somatoform dissociative symptoms were measured using 20-items self-reported Somatoform Dissociation Questionnaire (SDQ-20). 11 , 12 Normative score of the scale defines significant occurrence of somatoform dissociative symptoms for scores >30. Somatoform dissociative symptoms represent alterations in sensations of pain (analgesia, kinesthetic anesthesia), alterations of perception, loss of motor control, gastrointestinal symptoms, etc.…”
Section: Methodsmentioning
confidence: 99%
“…The last process through which complex traumatic stress may influence pain is through somatoform dissociation, which includes either increased pain perception or analgesia and has been linked to childhood trauma (particularly physical abuse) and traumatic stress in adults (Kukla, Selesova, Okrajek, & Tulak, 2010;Waller et al, 2000). One longitudinal study suggested that a critical period for the development of dissociation in children is during the preschool-age years (Macfie, Cicchetti, & Toth, 2001).…”
Section: Downloaded By [University Of Glasgow] At 16:19 20 December 2014mentioning
confidence: 98%
“…Nijenhuis and colleagues (1996) also created a short version SDQ-5 and suggested it might be used as a screening instrument. The SDQ-20 has been translated and used in several countries (Kukla et al, 2010;Mueller-Pfeiffer et al, 2010;Pullin et al, 2012). It contains 20 questions which are to be answered on a Likert-scale from 1-5 (Mueller-Pfeiffer et al, 2010).…”
Section: Instrumentsmentioning
confidence: 99%